Impact of teacher educational background on special education environment - Irvan, Muchamad; Putri, Anggita Hemaylia; Degeng, I Nyoman Sudana; Setyosari, Punaji; Degeng, Made Duananda Kartika (Specijalna edukacija i rehabilitacija, 2024)
Introduction. Schools for students with disabilities are one of the essential programs that the government should pay attention to. There are many aspects to consider in providing special education services, including the quality of learning. Teachers play a crucial role in the quality of learning for students with special needs. The role of teachers can be measured through their level of work involvement. Objective. The purpose of this study is to determine the level of work involvement of teachers in special and inclusive schools concerning the quality of learning. Method. We used the quantitative research method with descriptive statistical data analysis. The sample included 64 teachers from special education schools and 46 teachers from inclusive schools. Results. The study results show that teachers’ work involvement in schools for students with disabilities falls under the high category. In contrast, the work involvement of teachers in inclusive schools falls under the average category. Conclusion. It can be concluded that teachers in schools for students with disabilities are more optimal in fulfilling their roles in providing quality learning for children with special needs than teachers in inclusive schools.